A época em que meu tio morreu: a relação entre a mediação de socialidade e a memória - Marcello, Lorena Fonseca (2024)
While some events are forgotten after a few days, others mark the history of a city. However, the same news passes through people in different ways and intensities. This investigation deals with a reception study, whose objective is to analyze the relationship between the mediation of sociality and the memory of the collapse of the Andrea Building. In October 2019, in Fortaleza, a residential building collapsed, requiring a rescue operation for survivors and causing deaths. The incident generated commotion and gained repercussion in the local and national media, with coverage focusing on the action of firefighters in the rubble, the investigation into the cause of the collapse and its consequences. This investigation is based on the map of communicative mediations of culture, by Jesús Martín-Barbero, following the concepts of cultural matrices (Sunkel, 1987) and reception skills (Martín-Barbero, 1997), as well as addressing the notion of memory ( Halbwachs, 1990; Bosi, 1994; Pollak, 1992). As it was necessary to delve deeper into people's personal experiences and memories, in-depth interviews were conducted, with the aim of exploring the participants' daily lives and their news consumption habits. For this, six participants were selected: three of them were selected for their professions related to the areas of construction and condominium administration, the other three are residents of the Dionísio Torres neighborhood, where the Andrea Building was located. In the analysis, in addition to identifying language and content elements of the interviewees' responses linked to the rational-enlightenment and symbolic-dramatic cultural matrices, it was possible to observe the strong presence of images in the participants' memories related to the photos and videos that circulated in the coverage of the episode, the feeling of tragedy, the preference for television and social media to get information at the time and the strong memory of the cause of the collapse.